The Wild East Criminal Political Economics in South Asia - Harris-White, Barbara; Michelutti, Lucia (UCL Press, 2019)
The Wild East bridges political economy and anthropology to examine a variety of il/legal economic sectors and businesses such as red sanders, coal, fire, oil, sand, air spectrum, land, water, real estate, procurement and industrial labour. The 11 case studies, based across India, Pakistan and Bangladesh, explore how state regulative law is often ignored and/or selectively manipulated. The emerging collective narrative shows the workings of regulated criminal economic systems where criminal formations, politicians, police, judges and bureaucrats are deeply intertwined. By pioneering the field-study of the politicisation of economic crime, and disrupting the wider literature on South Asia's informal economy, The Wild East aims to influence future research agendas through its case for the study of mafia-enterprises and their engagement with governance in South Asia and outside. Its empirical and theoretical contribution to debates about economic crimes in democratic regimes will be of critical value to researchers in Economics, Anthropology, Sociology, Comparative Politics, Political Science and International Relations, Criminologists and Development Studies, as well as to those inside and outside academia interested in current affairs and the relationship between crime, politics and mafia enterprises.